DESIGN OF AN OVERLAY ON THE BAURENO HIGHWAY SECTION, BOJONEGORO REGENCY STA 89+700-91+700, USING THE MANUAL DESIGN METHOD FOR ROAD PAVEMENT 2017 (BINA MARGA) - Hidayatulloh, Mohamad Syarief Fateh; Moetriono, Hary (Fakultas Teknik Universitas Tanjungpura, 2023)
Roads as part of the National transportasion system have an important role, especially in supporting the economic, social and cultural, as well as environmental fields and developed through a regional development approach in order to achieve balance and equity in inter-regional development, form and strengthen national development (Law No. 38 of 2004 concering road).Bojonegoro Regency is one of the developing regencies in East Java, the acceleration of infrastructure development carried out by the Bojonegoro Regency Government is a form of effort to make the area more synergistic in order to achieve progress. Highway Baureno is a highway that uses flexible pavement and is one of the national roads that is passed by both motorcycles and heavy transport cars to go to the city of Lamongan. If from Bojonegoro, the density of vehicles on Jalan Raya Baureno causes road transportation problems caused by private vehicles.and heavy vehicles that have an impact on road conditions that are easily damaged, namely many cracked, potholed and bumpy roads. By looking at these conditions, it is necessary to plan an additional layer (Overlay) so as to expedite traffic and overcome existing problems.